The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1986
DOI: 10.1016/0035-9203(86)90340-8
|View full text |Cite
|
Sign up to set email alerts
|

Molluscicidal activity in the seeds of Millettia thonningii (Leguminosae: Papilionoideae)

Abstract: Seeds of the leguminous plant Millettia thonningii were shown to possess promising molluscicidal activity against Bulinus trunctatus. The size of the snails was an important determinant of their susceptibility to the molluscicide; specimens with shell lengths of 2 to 3 mm being more susceptible than snails 5 to 6 mm long.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

1989
1989
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 3 publications
1
15
0
Order By: Relevance
“…of the cephalopedal mass (Evans et al 1986, Duncan and Sturrock 1987, Molgaard et al 2000, Al-Zanbagi et al 2001) and confirmed, if on microscopic examination, there were no observable heartbeats (Marston and Hostettmann 1985). The numbers of dead and live snails were recorded.…”
Section: Bioassay For Molluscicidal Activitymentioning
confidence: 96%
See 2 more Smart Citations
“…of the cephalopedal mass (Evans et al 1986, Duncan and Sturrock 1987, Molgaard et al 2000, Al-Zanbagi et al 2001) and confirmed, if on microscopic examination, there were no observable heartbeats (Marston and Hostettmann 1985). The numbers of dead and live snails were recorded.…”
Section: Bioassay For Molluscicidal Activitymentioning
confidence: 96%
“…completely retracted into their shells (Evans et al 1986) they were discoloured (dos Santos et al 2000, Molgaard 2. et al 2000 or they were immobile and unresponsive to gentle prodding 3.…”
Section: Bioassay For Molluscicidal Activitymentioning
confidence: 98%
See 1 more Smart Citation
“…The solvents used include water (natural, synthetic, distilled, dechlorinated and/or boiled; Archibald, 1933;Ritchie et al, 1963;Evans et al, 1986;Alard et al, 1991;Lwambo and Moyo, 1991;Monkiedje et al, 1991;Ferrer Lopez et al, 1993;Yong and Rodriguez, 1994;Brackenbury and Appleton, 1997a, b), butanol (Spielman and Lemma, 1973;Lemma and Yau, 1974a), petroleum ether and dichlorom ethane (El Hadi et al, 1984;Appleton et al, 1992), hexane (Pereira et al, 1978), methanol (Silva and Rouquayrol, 1971;Alard et al, 1991), ethanol Shabana et al, 1988) and aqueous carboxym ethyl cellulose (Alard et al, 1991), amongst others. Most of the extraction procedures have involved the specialized use of expensive chem icals and equipment.…”
Section: Preparation Of the Crude Aqueous Plant Extractmentioning
confidence: 99%
“…Bioactive compounds found in extracts of the mature seeds of the West African legume Millettia thonningii, have been shown to have molluscicidal activity toward adult Bulinus truncatus and Biomphalaria glabrata (Evans et al, 1986) and B. glabrata egg masses (Tang, 1994;Tang et al, 1995).…”
Section: Introductionmentioning
confidence: 98%